But what do we mean by "health"? A critical perspective on the concept of health in the adolescent transition program of a Norwegian university hospital - Kjersti J. Ø. Fløtten; Isabelle Aujoulat; Vegard B. B. Wyller; Anne Lee Solevåg (BMC, 2022)
Abstract Background To understand better what influences the practice of our transition program, we wanted to explore the underlying theory of health. Methods We performed a qualitative content analysis of the written material that guides the program, comprising a quality system guideline, two checklists, a guide to health professionals and managers, and three patient brochures. Results The analysis resulted in the formulation of three themes; "Being on top of medical management", "Ability to promote own health" and "Awareness of own goals and expectations". Conclusion Our analysis indicates that the program content revolves mainly around medical management and that other dimensions of health are not emphasised. We question what the goals of the program are and if these goals are explicit and shared among the program stakeholders. An explicit program theory is vital and needs to be evident in material supporting transition programs.